2014
DOI: 10.1063/1.4862042
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication, and analysis of p-channel arsenide/antimonide hetero-junction tunnel transistors

Abstract: Articles you may be interested inUltrathin body GaSb-on-insulator p-channel metal-oxide-semiconductor field-effect transistors on Si fabricated by direct wafer bonding Appl. Phys. Lett. 106, 073503 (2015); 10.1063/1.4906922Operation of the GaSb p-channel metal-oxide-semiconductor field-effect transistors fabricated on (111) In this paper, we demonstrate InAs/GaSb hetero-junction (hetJ) and GaSb homo-junction (homJ) p-channel tunneling field effect transistors (pTFET) employing a low temperature atomic layer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…37 Further performance scaling of GeSn pTFET can be achieved with L G scaling and exploration of GeSn hetero-tunnel junction.…”
Section: Comparison Of Device Performance With the Reported Ptfetsmentioning
confidence: 99%
“…37 Further performance scaling of GeSn pTFET can be achieved with L G scaling and exploration of GeSn hetero-tunnel junction.…”
Section: Comparison Of Device Performance With the Reported Ptfetsmentioning
confidence: 99%
“…[1][2][3][4] It has been reported that the device performance has been improved significantly by utilizing a GaAs 0.35 Sb 0.65 layer in n-channel In 0.7 Ga 0.3 As/GaAs 0.35 Sb 0.65 staggered gap TFET structures when compared with In 0.7 Ga 0.3 As homojunction TFET device structures. 23,31 Meanwhile, it is equally important to develop high-performance p-type TFET devices within the same material system to enable complementary energy efficient logic circuits.…”
Section: A Strain Relaxation Properties Of Gaas 1-y Sb Y Metamorphicmentioning
confidence: 99%
“…[1][2][3][4] In a mixed As/Sb-based InGaAs/GaAsSb TFET structure, GaAs 1-y Sb y materials having a high Sb composition (>60%) are desirable for reducing the tunneling distance from the source to the channel. 3 The detailed strain relaxation state of each GaAs 1-y Sb y layer within each structure was analyzed from symmetric (004) and asymmetric (115) RSMs.…”
Section: A Strain Relaxation Properties Of Gaas 1-y Sb Y Metamorphicmentioning
confidence: 99%
See 2 more Smart Citations